‘De groote Petrus Nannius van Alkmaar’ Een mansportret door Cornelis Buys II in de collectie van het Stedelijk Museum Alkmaar geïdentificeerd - Taatgen, Alice (Studium, 2015)
This article describes the identification of an unknown scholar on a portrait in the collection of the Stedelijk Museum Alkmaar as Petrus Nannius, professor at the Collegium Trilingue of Louvain University between 1539 and 1557. The identification builds on significant similarities between this portrait and two printed variants. The use of the painting as the model for these prints, as well as its provenance, can be explained from Nannius’ social network, in which both the historian Petrus van Opmeer as the physician Petrus Forestus play an vital role.